2021
DOI: 10.1139/cgj-2020-0224
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale model tests of a single pile and two-pile groups for an offshore platform in sand

Abstract: Estimating pile group efficiency for open-ended steel piles in small group arrangements is a challenging task for designers. This paper reports on the large-scale experimental campaign performed for the BorWin gamma offshore converter platform, which involved single piles and two-pile group systems on a scale of 1:10. The experimental works included installation, dynamic end-of-driving tests, dynamic restrike tests, and static load tests of a single pile and a pair of two-pile groups in densely compacted, arti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…They reported a reduction in elastic response of the soil during longer thermal cycles. Foglia et al [27] conducted large-scale model tests of a single pile and two-pile groups for an offshore platform in sand. The study found that the pile spacing and pile group configuration significantly affect the bearing capacity and settlement of the energy pile group.…”
Section: Introductionmentioning
confidence: 99%
“…They reported a reduction in elastic response of the soil during longer thermal cycles. Foglia et al [27] conducted large-scale model tests of a single pile and two-pile groups for an offshore platform in sand. The study found that the pile spacing and pile group configuration significantly affect the bearing capacity and settlement of the energy pile group.…”
Section: Introductionmentioning
confidence: 99%
“…As the backfill of the foundation, the calcareous sand can not only shorten the construction period but also save landfill resources, which is of great significance for the development of the modern marine economy [ 16 ]. Reviewing literature revealed that the studies on the bearing characteristics of pile foundation mainly focuses on clay [ 17 , 18 , 19 ], ordinary sand [ 20 , 21 , 22 ], loess [ 23 ], saline soil [ 24 ]. and other areas [ 25 ].…”
Section: Introductionmentioning
confidence: 99%